A study of the effects of the mother-child relationship on the socialization process of individuals (children and adults) as seen in a comparative study of normal and abnormal families (families with and without identified patients) based on the systematic method of evaluating case history data - Ramfol, Anita Devi C (Department of Sociology, 2023)
The mother-child relationship has been 11 field of interest of a variety of educational disciplines. The subject has been studied from many viewpoints.